Coaching From the Sidelines: Examining the Impact of Teledebriefing in Simulation-Based Training. Issue 5 (October 2016) - Ahmed, Rami A.; Atkinson, Steven Scott; Gable, Brad; Yee, Jennifer; Gardner, Aimee K.
Abstract : Introduction: Although simulation facilities are available at most teaching institutions, the number of qualified instructors and/or content experts that facilitate postsimulation debriefing is inadequate at many institutions. There remains a paucity of evidence-based data regarding several aspects of debriefing, including debriefing with a facilitator present versus teledebriefing, in which participants undergo debriefing with a facilitator providing instruction and direction from an off-site location while they observe the simulation in real-time. We conducted this study to identify the effectiveness and feasibility of teledebriefing as an alternative form of instruction. Methods: This study was conducted with emergency medicine residents randomized into either a teledebriefing or on-site debriefing group during 11 simulation training sessions implemented for a 9-month period. The primary outcome of interest was resident perception of debriefing effectiveness, as measured by the Debriefing Assessment for Simulation in Healthcare-Student Version (See Appendix, Supplemental Digital Content 1, http://links.lww.com/SIH/A282 ) completed at the end of every simulation session. Results: A total of 44 debriefings occurred during the study period with a total number of 246 Debriefing Assessment for Simulation in Healthcare-Student Version completed. The data revealed a statistically significant difference between the effectiveness of on-site debriefing [6.64 (0.45)] and teledebriefing [6.08 (0.57), P < 0.001]. Residents regularly evaluated both traditional debriefing and teledebriefing as "consistently effective/very good." Conclusions: Teledebriefing was found to be rated lower than in-person debriefing but was still consistently effective. Further research is necessary to evaluate the effectiveness of teledebriefing in comparison with other alternatives. Teledebriefing potentially provides an alternative form of instruction within simulation environments for programs lacking access to expert faculty. Abstract : Supplemental digital content is available in the text.